Turkish Cultural Diplomacy and Yunus Emre Institutes: The Cases of North Macedonia and Serbia - Mehmet Ali Ugur; Ahmet Fethi Gun (Codrul Cosminului)
This study examines the cultural outreach initiatives of the Yunus Emre Institutes, which serve as a principal component of Turkish public diplomacy and a cornerstone of current Turkish foreign policy. Specifically, the research investigates the institute’s cultural projects during its first decade, with a particular emphasis on its efforts in the Balkan region. This study aims to demonstrate that Turkey’s public diplomacy campaign in the Balkans, bolstered by the diverse cultural initiatives of the Yunus Emre Institutes, has markedly improved Turkey’s image within the region. Through the institute’s active efforts, Turkey aims not only to preserve its historical and cultural ties with the countries of the region but also to cultivate favorable public opinion through a wide array of cultural programs, exhibitions, and Turkish language courses.